Analisis Peran Bawaslu dalam Pencegahan dan Penindakan Tindak Pidana Korupsi dan Pencucian Uang Kredit BPR Sebagai Dana Kampanye Pemilihan Umum - Yoga Permana; Rahma Shinta Azzahra; Nadia Najla Maharani Budiman (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
One of the roles of the Bank Perekonomian Rakyat (BPR) is to provide credit to improve the economic welfare of the lower middle class through micro and small business services. However, the provision of BPR credit is prone to misappropriation, one of which is used as an election campaign fund. This research is a legal research in analyzing the problem using literature study which is analyzed qualitatively. The results obtained from this research are that the misuse of BPR credit used as campaign funding can be suspected of being a criminal act of corruption and money laundering because it is obtained from state finances and there are indications of disguising and hiding money. The source of state finances provided to BPRs can be viewed in terms of state capital participation in the form of securities and the provision of facilities provided by the government. In anticipating campaign funds originating from criminal acts, the Badan Pengawas Pemilu must cooperate with other parties such as the Public Accounting Office to conduct campaign fund audits and related law enforcement officials such as the Pusat Penelusuran dan Analisis Transaksi Keuangan and the Corruption Eradication Commission to prevent and prosecute the use of money from corruption crimes for campaign funding.